Gold‐Catalyzed Rearrangement of Allylic Oxonium Ylides: Efficient Synthesis of Highly Functionalized Dihydrofuran‐3‐ones1. Issue 15 (6th March 2013) - Fu, Junkai; Shang, Hai; Wang, Zhaofeng; Chang, Le; Shao, Wenbing; Yang, Zhen; Tang, Yefeng
<x xml:space="preserve">Abstract</x> "Diazo" not needed: The title reaction results in the rearrangement of oxonium ylides, which were prepared from readily available homopropargylic allylic ethers instead of diazo compounds, through two different mechanisms: a concerted 2, 3‐sigmatropic rearrangement, or a stepwise 1, 4‐allyl migration followed by a Claisen rearrangement (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>